Kemampuan Menulis Cerita Pendek Siswa Kelas IX SMA Negeri 1 Raman Utara Tahun Pelajaran 2016/2017 - Ryan Mahendra; A. Effendi Sanusi; Bambang Riadi (FKIP Universitas Lampung, 2017)
The purpose of this study was to describe the students' ability in: (1) developing the theme of short story, (2) developing the short story, (3) developing the short story, (4) developing the background, and (5) delivering the message in the short story. This is a quantitative descriptive method. The results of the study on the ability to write short stories of students in grade XI SMA Negeri 1 Raman Utara lesson year 2016/2017, fall in the category of less with an average score of 49.87. The average score of perindicator students' abilities is: 1) average score theme is 72.22 good category; 2) average score figure is 61,66 medium category; 3) the background with an average of 61.66 medium category; 4) average score of 57,77 medium categories; and 5) mandate of average score is 67,77 good category.Tujuan penelitian ini adalah mendeskripsikan kemampuan siswa dalam : (1) mengembangkan tema cerpen, (2) mengembangkan tokoh cerpen, (3) mengembangkan alur cerpen, (4) mengembangkan latar, dan (5) penyampaian amanat dalam cerpen.Metode yang digunakan dalam penelitian ini adalah metode deskriptif kuantitatif. Hasil penelitian terhadap kemampuan menulis cerita pendek siswa kelas XI SMA Negeri 1 Raman Utara tahun pelajaran 2016/2017, tergolong dalam kategori kurang dengan skor rata-rata 49,87. Skor rata-rata kemampuan siswa perindikator adalah: 1) tema skor rata-rata yaitu 72,22 kategori baik; 2) tokoh skor rata-rata yaitu 61,66 kategori sedang; 3) latar dengan rata-rata yaitu 61,66 kategori sedang; 4) alur skor rata-rata yaitu 57,77 kategori sedang; dan 5) amanat skor rata-rata yaitu 67,77 kategori baik.Kata kunci: kemampuan, menulis, dan cerita pendek.